2019
DOI: 10.1016/j.conbuildmat.2019.02.093
|View full text |Cite
|
Sign up to set email alerts
|

Development of compression pull-off test (CPOT) to assess bond strength of bitumen

Abstract: The quantification of moisture susceptibility has been a major concern for researchers as it adversely affects the performance of asphalt pavements. Several methods have been developed to assess bond strength using asphalt mixture in loose or compacted state. These tests lack in their ability to study fundamental properties that the bond between bitumen and aggregate. In this context, pull-off stub techniques have been developed such as pull-off stub based tests and direct tension type tests. First group only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…The results showed that fibers led to an increased pull-off tensile strength of the mastics and changed the failure mode from cohesive to hybrid, implying an improvement in the cohesive strength of the mastic. Rahim, A. et al developed the compression pull-off test (CPOT) to study the cohesive and adhesive bond strength of binders [27]. They concluded that the COPT was useful for investigating the phenomenon of cavitation and fibrillary concentration in the cohesive bonds of asphalt and mastics.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that fibers led to an increased pull-off tensile strength of the mastics and changed the failure mode from cohesive to hybrid, implying an improvement in the cohesive strength of the mastic. Rahim, A. et al developed the compression pull-off test (CPOT) to study the cohesive and adhesive bond strength of binders [27]. They concluded that the COPT was useful for investigating the phenomenon of cavitation and fibrillary concentration in the cohesive bonds of asphalt and mastics.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional adhesive strength tests such as the pneumatic adhesion tensile testing instrument (PATTI) and BBS have certain limitations and have been continuously improved [23]. The compression pull-off test has been developed and proven to be excellent [37]. Considering the complexity of adhesion and the diversity of test methods, the adhesion mechanism of crumb-rubber-modified asphalt needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the other methods, Gan [24] pointed out that the pull-off test method could visually reflect the true adhesion strength with the advantages of simple and easy operations. Other studies [25,26] have also shown that the pull-off test is easy to observe and it could be used to determine the failure state of the asphalt-aggregate system by recording the magnitude of the bond strength. Considering the effect of aged asphalt and aggregates in RAP, Yan et al [27] used the coating treatment to simulate the RAP aggregate state and evaluated the adhesion of fresh asphalt binder to RAP aggregate by BBS test.…”
Section: Introductionmentioning
confidence: 99%